Use of the PCR-dgge technique to determine the microbial community in anaerobic activated sludges from biogas plants - Ladapa Kumdhitiahutsawakul (2019)
© 2019, All Right reserved. The PCR-DGGE technique was used to determine the microbial community in the activated sludge samples obtained from three different biogas plants using livestock including cows, chickens, and pigs as the substrates. Fourteen dominant bands of bacteria and eight bands of the archaea were observed. Most of the dominant bacterial groups were related to the uncultured bacteria collected from an anaerobic digester. The bacterial phyla in the activated sludge were Proteobacteria, Acidobacteria, Synergistetes and Bacteroidetes. Additionally, it was shown that three bands associated with the uncultured Acidobacteria clone, uncultured Aminanaerobia clone, and Geobacter sp. Methanogenic bacteria identified were found mainly in the orders (and genera) Methanobacteriales (Methanobacterium, Methanobrevibacter), Methanomicrobiales (Methanolinea) and Methanosarcinales (Methanoseata). The archaeal community showed that Methanoseata sp. dominated in the activated sludge sample from the biogas plant supplied with chicken and cow manure as the substrate, while Methanobacterium sp. and Methanobrevibacter sp. dominated in the activated sludge sample from pig manure. These results supported the approach of using PCR-based DGGE method to analyze the microbial community in the activated sludges. An understanding of these microorganisms will lead to management and improvement in biogas plant efficiencies.